A novel method for producing low cost dynamometric wheels based on harmonic elimination techniques. (February 2015) - Gutiérrez-López, María D.; García de Jalón, Javier; Cubillo, Adrián
Abstract: A method for producing low cost dynamometric wheels is presented in this paper. For carrying out this method, the metallic part of a commercial wheel is instrumented with strain gauges, which must be grouped in at least three circumferences and in equidistant radial lines. The strain signals of the same circumference are linearly combined to obtain at least two new signals that only depend on the tyre/road contact forces and moments. The influence of factors like the angle rotated by the wheel, the temperature or the centrifugal forces is eliminated in them by removing the continuous component and the largest possible number of harmonics, except the first or the second one, of the strain signals. The contact forces and moments are obtained from these new signals by solving two systems of linear equations with three unknowns each. This method is validated with some theoretical and experimental examples. Highlights: A method for producing low cost dynamometric wheels is presented. Strain gauges are bonded in the wheel grouped in circumferences and radial lines. The signals of each circumference are combined to obtain at least two new ones. The new signals only depend on the tyre/road contact forces and moments. The forces and moments are obtained by solving two systems of linear equations.